2022
DOI: 10.1177/10901981221090153
|View full text |Cite
|
Sign up to set email alerts
|

Urban-Rural Differences in Children’s and Adolescent’s Physical Activity and Screen-Time Trends Across 15 Years

Abstract: Background Urban and rural areas have been experiencing major demographic and structural changes, characterized by an aging population in rural areas and a growth of cities in number and size. However, it is poorly researched how children’s physical activity and screen time developed in urban and rural areas. To address this deficit, we investigated physical activity and screen-time trends in Germany’s pediatric population across four urbanicity levels (rural, small town, medium-sized town, city). Method We ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The research by Roemmich JN et al [21] showed that urban adolescents are more actively involved in PA, with a participation rate of 77.8%, while rural adolescents are only 22.2%. The results of the study by Nigg C et al [22] indicated that urban adolescents are more actively involved in PA and have a relatively more adequate level of PA. The differences in PA between urban and rural adolescents may be due to various factors.…”
Section: Discussionmentioning
confidence: 94%
“…The research by Roemmich JN et al [21] showed that urban adolescents are more actively involved in PA, with a participation rate of 77.8%, while rural adolescents are only 22.2%. The results of the study by Nigg C et al [22] indicated that urban adolescents are more actively involved in PA and have a relatively more adequate level of PA. The differences in PA between urban and rural adolescents may be due to various factors.…”
Section: Discussionmentioning
confidence: 94%
“…The smallest changes occurred among 16–17-year-old girls and 14–15-year-old boys, where no significant shift in the reduction of hours spent outdoors was observed. Nigg et al (2022) also noted a decrease in the time spent outdoors among adolescents and, at the same time, an increase in screen time [ 15 ]. Distance learning during the restrictions caused by the COVID-19 pandemic also contributed to the increase in screen time and, therefore, to the decrease in outdoor time.…”
Section: Discussionmentioning
confidence: 99%
“…It is encouraging to observe that, according to the HBSC (Health Behaviour in School-aged Children) study, the physical activity levels among school children have been relatively stable in recent years [ 12 , 13 ]; meanwhile, boys are more likely to meet the recommended daily physical activity levels than girls, and younger school students (11 years old) are more physically active than older ones (15 years old) [ 12 , 13 , 14 ]. Additionally, over the past two decades, leisure time physical activity has declined among both rural and urban children, with a particularly significant decrease in the time rural children spend outdoors [ 15 ]. At the same time, the sedentary screen time for both rural and urban children has increased [ 13 , 15 , 16 ], and this in turn limits physical activity [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no significant difference in the total levels of physical activity of adults living in rural and those living in urban areas, adults in rural areas have lower levels of transport-related physical activity, which can be explained by longer travel distances to workplaces, shops, and other facilities and destinations ( 34 , 60 , 61 ). While older studies have found higher levels of physical activity in children and adolescents in rural compared to urban areas in Germany, a more recent one revealed stronger declines of total physical activity and outdoor play in rural areas, which may be a result of a lack of opportunities ( 62 65 ).…”
Section: Introductionmentioning
confidence: 91%